THE RESILIENCE OF SHARIA-COMPLIANT AND CONVENTIONAL MSMES IN FACING DIGITAL DISRUPTION IN MEDAN: AN ANALYSIS OF STRATEGIES AND MAQASID SHARIA - Muslim Marpaung; Helvinasari Nasution; Inayatul Widad Nasution; Widya Khaidir (RADJA PUBLIKA, 2026)
Digital transformation has become inevitable for micro, small, and medium enterprises (MSMEs) in Indonesia. However, MSMEs' preparedness and resilience to digital disruption still vary. According to data from the Ministry of Cooperatives and SMEs, more than 64 million MSMEs contribute 60% of the national Gross Domestic Product (GDP), yet only a small portion are truly digitalized. This study aims to analyze the differences in resilience between Sharia-compliant MSMEs and conventional MSMEs in Medan City in facing digital disruption, by examining aspects of adaptation strategies and the values of Maqasid Sharia. This research method uses a qualitative-descriptive approach through literature analysis, semi-structured interviews, and secondary data from official government reports and scientific publications. The research results show that conventional MSMEs are quicker to adopt digital technology, while Sharia MSMEs have more stable social resilience and customer loyalty due to their ethical and trust-based foundation based on Islamic principles. The implications of this research demonstrate the importance of integrating Maqasid Sharia values into MSME digitalization strategies to achieve sustainable economic resilience.